Liquid Moisture Transport in Knitted Fabrics in Relaxed and Stretched State - Malgorzata Matusiak; Otgonsuren Sukhbat (Communications in Development and Assembling of Textile Products)
The aim of this work was to analyze the influence of stretch on liquid moisture transport through the knitted fabrics for T-shirts. Five variants of cotton and cotton blended fabrics were measured by means of the Moisture Management Tester. Measurements have been performed for samples in the unstretched state and samples stretched by 15%. To precisely stretch the fabrics, the MMT Stretch Fabric Fixture has been applied. The results have been analyzed statistically in order to assess the influence of stretch on the parameters characterizing the moisture transport through the fabrics.